Analisis Pengaruh Tingkat Konsentrasi Pasar Terhadap Efisiensi Industri Pengolahan Besar Dan Sedang Di Jawa Timur - Widita Pambudi Wijaya; Dyah Wulan Sari; Wenny Restikasari (MediaTrend, 2021)
This study aims to investigate the effect of market concentration on industrial efficiency. Large and medium processing industry data in East Java and the Stochastic Frontier Analysis (SFA) approach were used to investigate the impact of market concentration on the efficiency of the industry. The results of the study indicate that market concentration in the processing industry in East Java leads to oligopoly. The variable of firm size (FSize) and the level of market concentration (CR4) have a negative effect on the level of technical efficiency of large and medium industries in East Java.